STUDY OF PLASMA ION NITRIDING OF AISI H13 STEEL - Souza, M. C. L.; Silva, G. R. da; Souza, E. S.; Pinto, W. C. L.; Tapanes, N. C. O. (Revista de Engenharia Térmica, 2020)
This work studied the thermochemical treatment of AISI H13 steel used for extrusion of aluminum parts, by plasma ionic nitriding, with the objective of increasing the surface hardness of the mold, by forming an external layer of stable nitrides, increasing the resistance to wear, fatigue, corrosion and thermal resistance. Because it uses ions, plasma ion nitriding is more efficient than liquid and gas nitriding. This process is widely used for ferrous materials and aluminum. The main applications are for extrusion, material injection molds, cutting tools and automotive parts. In this work, samples of the AISI H13 steel were nitrided to be used as aluminum injection molds. The treatment was carried out at 300 oC in a sodium cyanide bath, for a period of 6 h at a pressure of 15 mTorr (2 Pa). The gaseous mixture inside the nitreter consisted of 80% N2 + 20% H2. After treatment, Vickers hardness measurements reached surface values of 963 HV. The results at the end of the treatment showed a 122 µm nitrided layer.